Epidemiology of childhood-onset type 1 diabetes in Azerbaijan: Incidence, clinical features, biochemistry, and HLA-DRB1 status. (October 2018) - Ahmadov, Gunduz Ahmad; Govender, Denira; Atkinson, Mark Alvin; Sultanova, Rumiyya Anvar; Eubova, Amalia Abdulla; Wasserfall, Clive Henry; Mack, Steven John; Lane, Julie Ann; Noble, Janelle Annette; Ogle, Graham David
Abstract: Aims: Determine the incidence and typology of diabetes in children in Azerbaijan. Methods: Clinical features, C-peptide, autoantibodies (glutamic acid decarboxylase 65 (GAD65) and islet antigen 2 (IA-2)), and HLA-DRB1 status were studied in 106 subjects <18 years of age who were recently diagnosed. 104 cases were consecutive. Incidence was determined for Baku and Absheron regions, where ascertainment is estimated to be essentially 100%. Results: 104 of the 106 (98%) were diagnosed with type 1 diabetes, one with type 2 diabetes and one with atypical diabetes. Type 1 diabetes incidence in Baku City and Absheron was 7.05 per 100, 000 population <15 years per year. Peak age of onset was 10 years. There was a slight male preponderance (male:female 1.17:1), and no temporal association with seasons. Almost all type 1 diabetes subjects presented with classic symptoms including a high incidence (58%) of diabetic ketoacidosis. 86% presented with low C-peptide values (<0.13 nmol/L, <0.40 ng/mL) and 74% were positive for at least one type 1 diabetes-related autoantibody. Conclusions: Azerbaijan has a moderate type 1 diabetes incidence and clinical, biochemical and genetic features similar to that in European populations.